Efecto de la Levadura de cerveza (S. cerevisiae) asociada con vitamina E sobre las variables productivas y la calidad de la canal de pollos parrilleros - Linares, M.J. (2009)
The aim was to estimate the action of yeast (S. Cerevisiae) - vitamin E combinated or not over the productive variables and quality carcass. One hundred and twenty male broilers Cobb received the following diets: Control, Vitamin 1 (V1, 50 ppm E vitamin), Vitamin 2 (V2, 100 ppm E vitamin), Vitamin 3 (V3, 200 ppm E vitamin) and Yeast plus Vitamin (Y+V, 0,3 % yeast + 200 pp E vitamin) with six chicken per pen and four pen for ration Since 29 till 52 days old the Average Daily Consumption (ADC), Average Daily Gain (ADG) and Conversion Index (CI) were measured. % carcass yield (CY), % breast weigh (BW), % leg muscles weigh (LMW) and % fat weigh (FW) were determinated. An ANOVA and a tukey test were made, significant differences were considered if p 0,05. The broiler that received the combination of yeast and E vitamin had significantly best CI and hight LMW and lower FW than the others. It could be concluded that yeast + E vitamin increased productive performance and carcass quality because had better CI, increased LMW and reduced FW in the broiler that received it.